2008
DOI: 10.1002/mrd.20964
|View full text |Cite
|
Sign up to set email alerts
|

Release of DEFB126 from macaque sperm and completion of capacitation are triggered by conditions that simulate periovulatory oviductal fluid

Abstract: Capacitation of macaque sperm in vitro has been achieved efficiently only with the addition of both cyclic nucleotides and methylxanthines. The use of these exogenous sperm activators clouds an understanding of the normal mechanisms underlying capacitation and may slow early embryo development following in vitro fertilization (IVF). We demonstrate that culture medium which simulates periovulatory oviductal fluid with respect to bicarbonate (HCO(3)(-)) and glucose concentration induces capacitation in a high pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 96 publications
(103 reference statements)
1
11
0
Order By: Relevance
“…Studies in non-human primates have shown that DEFB126 is a major component of the sperm surface glycocalyx and is important for normal sperm function, including efficient sperm trafficking in the female reproductive tract (15, 16, 17, 18, 19, 45, 46). We now report that a mutation in human DEFB126 is common in each of several disparate population cohorts interrogated (allele frequency 0.44-0.61).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in non-human primates have shown that DEFB126 is a major component of the sperm surface glycocalyx and is important for normal sperm function, including efficient sperm trafficking in the female reproductive tract (15, 16, 17, 18, 19, 45, 46). We now report that a mutation in human DEFB126 is common in each of several disparate population cohorts interrogated (allele frequency 0.44-0.61).…”
Section: Discussionmentioning
confidence: 99%
“…It is the negative charges on DEFB126 on the sperm surface that allow sperm to move through the cervical mucus, which is enriched in anionic glycosaminoglycans 9 . Upon capacitation, DEFB126 is released from the sperm surface 9 42 . If del / del mutation results the loss of DEFB126, the level of sialic acid has to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this possibility includes the observation that soluble oviductal factors enhance capacitation of bull sperm (Chian et al 1995). Also, incubating macaque sperm in medium containing the levels of bicarbonate and glucose found in periovulatory oviduct fluid capacitates the sperm and releases oviduct-binding DEFB126 from the sperm surface (Tollner et al 2009). …”
Section: Molecular Interactionsmentioning
confidence: 99%